Bcl-2 expression in colorectal tumors: evidence of different pathways in sporadic and ulcerative-colitis-associated carcinomas. - Ilyas, M; Tomlinson, I; Hanby, A; Yao, T; Bodmer, W; Talbot, I (1996)
Colorectal cancers (CRCs) differ in their age at presentation, distribution, histological features, and prognosis. If tumor biology reflects genetic events, these tumors might be expected to show differences in their genetic pathways. In this study, we investigated the role of Bcl-2 in the development of three different tumor groups. Using markers at eight different microsatellite locl, we characterized one group of 34 left-sided sporadic CRCs as replication error negative (RER-) and another group of 18 left-sided sporadic CRCs as replication error positive (RER+). These tumors, together with a third group of 22 left-sided ulcerative-colitis-associated CRCs (UCACRCs), were then examined by immunohistochemistry for Bcl-2 overexpression. Of 34 of the RER- tumors, 21 (62%) and 10 of 18 (56%) of the RER+ tumors were positive for Bcl-2 overexpression. In contrast, only 5 of 22 (23%) of the UCACRCs showed similar overexpression. Our results show a significantly lower frequency of Bcl-2 overexpression in UCACRCs as compared with sporadic CRCs (P < 0.005) but no difference between sporadic left-sided RER+ and RER- CRCs. These data provide additional evidence that UCACRCs may develop along a pathway that is different from that of sporadic CRCs.